Storytelling as a Way of Convincing Audiences in Environmental Journalism - Ana Nadhya Abrar (Ikatan Sarjana Komunikasi Indonesia, 2018)
Indonesian press will continue to broadcast environmental news. From the journalism point of view, the news must be clear, understanable, and complete. However, for the time being, the result is not optimal. Audience is still unsure of the environmental news that reaches them. Their emotions are not touched by the environmental news, so they can not contribute to solving environmental problems. Based on this fact, come up idea to make storytelling as a way to convince audience in environmental journalism. Before implementing this concept, the writer conducted research on storytelling practices in broadcasting news of forest and land fires (karhutla) in Riau Pos. Evidently Riau Pos, who had received an award from the provincial government of Riau, has not practiced storytelling in broadcast karhutla news. This fact reinforces the writer to propose storytelling as a convincing art in environmental journalism. This concept leads to a narrative style that takes into account the nature of writing, target of writing, news angles and news languages by presenting the news from the perspective of journalists.